Prevalence and Risk Factors for Human Immunodeficiency Virus (HIV) and Syphilis Infections Among Military Personnel in Sierra Leone - Audrey Djibo, Djeneba; Sahr, Foday; Allen McCutchan, J.; Jain, Sonia; Rosario G. Araneta, Maria; K. Brodine, Stephanie; A. Shaffer, Richard (Current HIV Research, 2017)
Context: HIV and syphilis infections are common in military personnel in sub-Saharan Africa, which impact combat preparedness and increase demands on the military health care system. The prevalence of HIV is estimated at 1.5% among the general population (15-49 years of age) of Sierra Leone, and the estimated syphilis prevalence ranged from 1.5% to 5.2% based on regional studies. We examined the prevalence and risk factors for these two common sexually transmitted infections in the Sierra Leone military personnel. Methods: This cross-sectional study examined 1157 randomly selected soldiers from the Republic of Sierra Leone Armed Forces in 2013 using computer-assisted personal interviews and rapid testing algorithms. Descriptive statistics and logistic regression models were implemented to identify risk factors for HIV and syphilis separately. Results: The mean age of participants was 38 years, 11.1% were female, and 86.5% were married. The seroprevalence of HIV and syphilis were 3.3% (95% confidence interval [CI]: 2.3%-4.3%) and 7.3% (95% CI: 5.9%-8.8%), respectively. Lower educational attainment in women, multiple sexual partners, unintended sex after alcohol use and use of condoms were independently associated with HIV status (p<0.05). After adjustment, HIV infection was associated with female gender, unintended sex after alcohol use, condom use at last sex, having multiple sexual partnerships in the same week and HIV testing outside of military facilities (p<0.05). Increasing age, positive HIV status and rural regions of residence were associated with syphilis seropositivity. Conclusion: The prevalence of sexually transmitted infections among military personnel was higher than the general population of Sierra Leone. Several high-risk sexual behaviors that expose soldiers to HIV and syphilis could be addressed through prevention interventions.
Keywords: military